2011
DOI: 10.1007/s12011-011-9241-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oral Consumption of Selenium Nanoparticles on Chemotactic and Respiratory Burst Activities of Neutrophils in Comparison with Sodium Selenite in Sheep

Abstract: The present study was designed to compare the effects of nano-selenium and of sodium selenite on the chemotactic and respiratory burst activities of neutrophils in sheep. Fifteen sheep were randomly divided into three groups. Groups 1 and 2 received selenium nanoparticles (1 mg/kg) or sodium selenite (1 mg/kg) orally, respectively, for ten consecutive days, and the third group was considered as the control. To determine the chemotactic and respiratory burst activities of the neutrophils, the leading front assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 34 publications
(43 reference statements)
3
18
0
1
Order By: Relevance
“…We note that results from our study and from published results showed that the same toxicity endpoints are affected by both SeNPs and dissolved ionic Se species (Zhang et al 2001, Jia et al 2005, Wang et al 2007, Benko et al 2012, Kojouri, Sadeghian, et al 2012, Hadrup et al 2016). An explanation for this could be that SeNP are dissolved in the mammalian body to exert an effect similar to that observed for dissolved selenite.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We note that results from our study and from published results showed that the same toxicity endpoints are affected by both SeNPs and dissolved ionic Se species (Zhang et al 2001, Jia et al 2005, Wang et al 2007, Benko et al 2012, Kojouri, Sadeghian, et al 2012, Hadrup et al 2016). An explanation for this could be that SeNP are dissolved in the mammalian body to exert an effect similar to that observed for dissolved selenite.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, in a previous study based on the same animal experiment we found that both Se formulations displayed similar effects on the general urine metabolome as indicated by partial least squares discriminant analyses, with specific differences in such putative identified metabolites as decanedioic acid and hydroxydecanedioic acid (Hadrup et al 2016). Data from other studies show that ionic forms of Se exert toxicity at lower doses as compared to SeNPs (Zhang et al 2001, Jia et al 2005, Wang et al 2007, or that equal or almost equal effects occur following dosage of the two formulations (Benko et al 2012, Kojouri, Jahanabadi, et al 2012, Kojouri, Sadeghian, et al 2012. Combined with results from our study, the available data did not lead to any firm conclusion on whether SeNPs are less or more toxic as compared to dissolved Na selenite, i.e.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Data from others are also in line with this. Similar effects of Se nanoparticles and sodium selenite on iron, transferrin and on neutrophils have been observed in sheep ( Kojouri et al, 2012a ; Kojouri et al, 2012b ). In contrast, a higher biological effect of Se as selenite ions as compared to nanoparticles has been reported in other studies.…”
Section: Discussionsupporting
confidence: 74%
“…Reportes indican que esta actividad biológica es comparable a la que muestran el selenito, el seleniato o bien algunas formas orgánicas de selenio (selenometionina, selenocisteína, etc.) (Kojouri et al 2012 por lo que son una alternativa para reemplazar a cualquiera de estas especies actualmente utilizadas como suplementos de selenio en distintos países.…”
Section: Introduccionunclassified